Hybrid renewable energy systems sizing for offshore multi-purpose platforms - Recalde, Luis; Yue, Hong; Leithead, William; Anaya-Lara, Olimpo; Liu, Hongda; You, Jiang (Volume 10: Ocean Renewable Energy, 2019)
Integrating marine renewables and aquaculture is a complex task. The generated power of each renewable technology depends on its source cycle (wind, wave, solar PV), leading to periods of zero power production. On the other side, aquaculture farms require smooth and stable power supply since any power shortage can lead to the loss of the entire farm production. This paper illustrates the sizing of a hybrid energy system (wind,solar PV, energy storage) to power up the aquaculture farm. The sizing is based on available commercial technology and the system is mounted on a single multi-purpose platform. Reliability is improved by considering device redundancies. Such hybrid system has not been considered before for aquaculture farms. System rough sizing, based on simple online renewable energy calculators, is used to select existing renewable technologies and HOMER Pro simulation software is used to evaluate the technical and economic feasibility of the microgrid for all possible combinations of the technology selected and perform sensitivity analysis on wind turbine tower height, battery state of charge and solar PV panels reflectance. The optimisation is subject to combined dispatch strategy and net present cost.